The Basic Determinants of Malnutrition: Resources, Structures, Ideas and Power - Jody Harris; Nicholas Nisbett (Kerman University of Medical Sciences, 2021)
BackgroundWhile child undernutrition is improving overall, different population groups are experiencing different outcomes. What sets some groups apart is their experience of the 'basic determinants' of malnutrition, that underpin the 'immediate' and 'underlying' determinants, and that have been much less studied, defined and understood. MethodsWe undertook a qualitative narrative review based in two sets of ideas: nutrition's basic determinants as laid out in the original United Nations Children's Fund (UNICEF) framework, and critical concepts emerging from development studies. These ideas informed searches in Google Scholar, and resulting papers formed the basis for the review. ResultsBased on this literature, we expand and clarify the terminology of 'basic determinants' into a new framework, to include (1) resources and (material, human, social and natural) capitals at the basic level; (2) structures including social, market, legal and political systems driven by long-term demographic, economic, and environmental trends; and (3) ideas, beliefs and ideologies prevailing within a given society - crystallising into social norms and institutions - fundamentally shaping how societies are structured around power and marginalisation. We then illustrate with existing literature how these basic factors play out in the food, health and care determinants of malnutrition; and how theories of human rights and collective commons point us towards practical redressal options through improved participation and accountability. ConclusionWe show here that the basic determinants are not a black box of 'context,' but can be broken down into comprehensible issues that are amenable to change, and should be considered explicitly in research and action to reduce the global burden of malnutrition.